2006
DOI: 10.1111/j.1523-1739.2006.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Success of Captive‐Bred Steelhead Trout in the Wild: Evaluation of Three Hatchery Programs in the Hood River

Abstract: Population supplementation programs that release captive-bred offspring into the wild to boost the size of endangered populations are now in place for many species. The use of hatcheries for supplementing salmonid populations has become particularly popular. Nevertheless, whether such programs actually increase the size of wild populations remains unclear, and predictions that supplementation fish drag down the fitness of wild fish remain untested. To address these issues, we performed DNA-based parentage anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
187
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(201 citation statements)
references
References 30 publications
10
187
3
Order By: Relevance
“…These data (real parents with simulated offspring) were then used to conduct a parentage analysis and to compare the relative fitness estimates produced by the most likely, threshold, and fractional assignment methods. Observed distributions of relative fitness in salmon often appear approximately exponentially distributed (Seamons et al 2004;Ford et al 2006;Araki et al 2007a), so fitness in the simulations was based on an exponential distribution. Specifically, each parent was assigned an initial fitness value drawn randomly from an exponential distribution with a mean of 1.…”
Section: Methodsmentioning
confidence: 99%
“…These data (real parents with simulated offspring) were then used to conduct a parentage analysis and to compare the relative fitness estimates produced by the most likely, threshold, and fractional assignment methods. Observed distributions of relative fitness in salmon often appear approximately exponentially distributed (Seamons et al 2004;Ford et al 2006;Araki et al 2007a), so fitness in the simulations was based on an exponential distribution. Specifically, each parent was assigned an initial fitness value drawn randomly from an exponential distribution with a mean of 1.…”
Section: Methodsmentioning
confidence: 99%
“…Araki et al [79] monitored a supplementation program for steelhead (anadromous Oncorhynchus mykiss; Figure I) in Oregon and found that the relative reproductive success of hatchery fish improved when the program phased out the non-native hatchery stock and began using local native fish for brood stock. Monitoring the genetic contribution of captive individuals to natural populations is necessary before one can assess how the captive program affects the N e of the combined captive-wild system [50,80].…”
Section: Monitoring Recruitment In Wild Populationsmentioning
confidence: 99%
“…PBT is commonly used in other salmonid systems to monitor how integrated hatchery practices affect the reproductive success of salmon that spawn in rivers. For example, this research tool has shown that when hatchery-origin steelhead spawn with natural-origin steelhead in the wild, the natural-origin fish can experience a 40% reduction in the number of progeny produced (Araki et al 2007 trade-off between fitness effects from the three-fold increase in hatchery production of SRWRC during drought years when survival of natural juveniles from the Upper Sacramento River was exceptionally low, and the rescue role the hatchery may play in overall population abundance. Figure 12).…”
Section: Application Examplesmentioning
confidence: 99%
“…A comprehensive sampling design is needed to assess the effects of water-project operations and domestication selection on reproductive success in SRWRC, given the on-going challenges with watertemperature management during periods of drought and the recent increase in hatchery production. The PBT technology is routinely used to monitor salmonids in other systems, and it is used in broodstock management for spring-run Chinook Salmon in the Feather River Hatchery within the Central Valley (Araki et al 2007;Chilcote et al 2011;Steele et al 2013;Christie et al 2014;CDFW 2016). Tissue samples currently being collected during in-river carcass surveys for SRWRC and broodstock at LSNFH serve as a ready-made library of parental genotypes for natural-origin and hatchery populations.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation